The Role Of Serotonin In The Cognitive Function Of The Elderly : A Literature Review - Rifqi Hamdani Pasaribu; Muhammad Ichwan; Aldy Safruddin Rambe; Ririe F. Malisie; Sry Suryani Widjaja (Talenta Publisher, 2023)
The last few decades have seen an increase in the number of elderly populations around the world. One consequence of an aging population is an increased incidence of impaired cognitive function. Serotonin, or 5-hydroxytryptamine (5-HT), is found to be involved in many physiological or pathophysiological processes including cognitive function. Alterations in serotonin (5-HT) function have been hypothesized to underlie a range of physiological, emotional, and cognitive changes in eldery. This paper provide reviews and references that a serotonin plays a role in the cognitive function of the elderly.